Genetic improvement of sorghum at INIFAP - García, Noe Montes; Quintero, Victor Pecina; Alanis, Héctor Williams; Martínez, Miguel Hernández; López, Ma. Eugenia Cisneros; Gallegos, Tomás Moreno (Revista Mexicana de Ciencias Agrícolas, 2021)
In Mexico, genetic improvement of sorghum began in 1944 at the Office of Special Studies. Later, improvement activities were carried out in three regions with the introduction of genetic material from which lines were derived and the first adapted sorghum hybrids were generated. The program has focused on the generation of genetic material for several niche markets including balanced food, food for human consumption and biofuel production. Among the genetic materials, the hybrid RB-3030 stands out for having been the one with the highest production by PRONASE at the time. To date, 36 hybrids and varieties have been generated, of which 12 are currently being used, among which the red-orange bean sorghums RB-Norteño and RB-Huasteco and the white sorghum variety RB-Paloma stand out. As well, the forage sorghum Sinaloense 202 and Gavatero-203 stand out. On the other hand, the sorghum RB-Cañero, RB Cañaveral, RB Tehua and RB-Pirulí have been formed for bioethanol production. In addition, there are parental lines of hybrids that are acquired by companies for the production of certified seed. There are several challenges such as increasing production, but in the short term it is necessary to increase the promotion and marketing of genetic materials, and in the medium term to strengthen research in disease control, tolerance of draughts and salts, and obtain varieties with better nutritional and energy quality.
Keywords: seeds; tolerance; varieties